Saberes e práticas que decolonizam a ciência e o conhecimento : construções narrativas (auto)biográficas de docentes da UFMG - Ricardo Dias de Castro (2022)
This doctoral thesis is situated, in a context, in which it is possible to recognize that the university space coexists, in a publicly conflicting way, with a plurality of perspectives on the pedagogical routines of public higher education, research themes in the field of science , ways of research-teaching-extension know-how and corporate dynamics. Against the university's conservative stance and in the dispute for a radically democratic regime for the production of knowledge, science and intervention in the direction of society; fields such as anti-racism, feminism, critical knowledge/doings, affirmative actions and decoloniality have been protagonists in resistance to the Modern/Colonial System of Gender. In this way, it is certain that some professors do not abandon Western research or (almost) everything that has been produced, in recent centuries, from the mainstream matrices of Euro, white, bourgeois, patriarchal and heterocisnormative knowledge. Thus, public higher education professors have placed limits on the colonial, racist, sexist, classist and cosmophobic project forged in the epistemic monolatries of Modern Science. Soaked in this atmosphere, we propose the objective of this research to understand how public higher education professors produce knowledge and actions that decolonize knowledge, science and society within the scope of the Federal University of Minas Gerais. Through the (auto)biographical narrative reports of ten UFMG professors with whom we spoke, we were able to analyze the countless contradictions that appear in a public university with a modern/colonial history that, based on its fractured locus, is capable of moving epistemic and political ruptures in the reinvention of a new world that is already possible despite the traps of coloniality. Through the analyses, we observed that there is a very large heterogeneity in relation to how the desire for the life of a teacher was being built in these trajectories. Which points to the importance of questioning power systems that continue to produce certain accesses and/or impediments for some people to realize their academic dreams. Regarding the political-pedagogical strategies, which are adopted to make the modern/colonial hegemony in public universities falter, we could observe that these professors embrace a model of education, radically, transdisciplinary. And so, they do so by recognizing the limitation of their own fields of knowledge as a response to the problems that science poses/produces for/from society. As a marginal practice, extension is central to the trajectory that the subjects of this research were weaving at UFMG. The inseparability between teaching, research and extension is a daily reality among these professors. Everyone, therefore, is committed to the production of knowledge that dialogues with the community outside the institutional framework of the public university. In this sense, definitely, the public university does not have the same atmosphere of its founding years. This is because Affirmative Actions institutionalized desires to transform centuries of anti-racist and popular resistance that became public policies in the 21st century. Professors point out that quotas and affirmative actions, in this direction, need to be, more than a meritocratic reservation of vacancies, a decolonial epistemic turn. In addition to the policy of reserving vacancies for indigenous people, blacks/blacks, the poor and people with disabilities, the affirmative semantics builds a climate of solidarity with other, historically subordinated groups. In this sense, more than thinking about an academic and social project for you; these professors are mobilized by collective causes and this moves them to be in spaces of power and decision. Between criticizing and endorsing the public university, these professors invent an in-between worlds that does not totalize traditional knowledge, nor does it naturalize Western knowledge. In this context, the university is identified as a hostile place, but because it is public, it has a democratic power and a decolonial force that, in the past, would be unimaginable. What is possible through the radical interpellation of laws, norms, affections, aesthetics and the colonial heterocisnormative form of modern reason. Something that is facilitated by the permanence of academic freedom and university autonomy in the educational public service. It is important, then, to recognize that the public university is already producing new forms of knowledge, pedagogical practices, affections, desires, constructions of trajectories and reorganization of parameters for the designation of legitimate knowledge. Something that is built by a political interest in the diversity of the world and in the various ways we can think-change projects that coexist in the cosmological infinity that inhabits the pluri-verse.